Implementasi Pengamanan Citra Digital Menggunakan Algoritma ICE - Josua Alfiandi Sinuhaji (Universitas Budi Darma, 2020)
Digital imagery is currently very widely used, so it is very vulnerable to data theft by unauthorized parties. In order to maintain the security of digital images can be done by using cryptographic techniques. Cryptographic techniques can encode digital images by encrypting them in the form of passwords that are not understood. ICE is a block cipher published by Kwan in 1997. This algorithm has a structure similar to DES, but with additional bit permutations that do not depend on the key in the rotation function. There are various types of ICE variants, namely Thin-ICE, ICE standard, and ICE-n. The difference between the three is the length of the keyword used and the number of rounds. The Thin-ICE algorithm uses 64 bits and 8 turns. The ICE standard uses 64 bits and 16 round keys. The ICE-n algorithm uses keys 64n bits and 16n turns. The use of this type of algorithm can be adjusted to the needs of users where Thin-ICE has the lowest level of security among the three, while ICE-n is the highest. This algorithm does not become the subject of a patent and the source code can be used freely.Keywords : Cryptography, Digital Image,Algorithm,ICE.